Pergolakan Andi Azis di Makassar - Bustan Buhari (Rayhan Intermedia, 2017)
Andi Azis was born in Barru, South Sulawesi 19 September 1924. He had attended Europe Leger School but was not finished. Andi Azis was later taken by a Dutch Resident Assistant Resident to the Netherlands. Andi Aziz by many people is believed to be a member of the military with a good person but in the scale of military unity KNIL in South Sulawesi itself more inclined as a puppet. Colonel Schotborg and Sumokil are the main controllers of KNIL force in Makassar City. When the Andi Aziz rebellion in Makassar, to anticipate the RIS Government in Jakarta has formed a joint forces Expedition East Indonesia. These troops consist of battalions from West Java, Central Java and East Java supported and Police. Commander of the Command appointed Colonel Kawilarang Panglima.